2018
DOI: 10.1155/2018/9247439
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity Parameters Associated with Gastrointestinal Tract Nematodes in Sheep in Dabat District, Northwest Ethiopia

Abstract: Gastrointestinal nematode (GIN) infections of sheep and their interaction with selected morbidity parameters were studied in smallholder farms. 120 faecal samples were collected and examined using faecal flotation to determine nematode infection in sheep. Thus, the study demonstrated overall prevalence of 57.5% GIN infections, while the mean faecal egg count (FEC) was 517.5 EPG. The severity of GIN infection was determined based on EPG as a mild infection (EPG <500), 55.1%, moderate infection (EPG = 500–1500),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 26 publications
3
11
0
Order By: Relevance
“…Due to the morphological similarity of Strongyloides eggs, the possibility of errors in the species identification cannot be ruled out. Nevertheless, this could still be a preliminary presentation of the species responsible for gastrointestinal parasite infections in this region as the dominant species reported here were consistent with most other regions [1,2,3,39]. The GIN and coccidia infection rates revealed in this study were relatively high.…”
Section: Plos Onesupporting
confidence: 88%
See 1 more Smart Citation
“…Due to the morphological similarity of Strongyloides eggs, the possibility of errors in the species identification cannot be ruled out. Nevertheless, this could still be a preliminary presentation of the species responsible for gastrointestinal parasite infections in this region as the dominant species reported here were consistent with most other regions [1,2,3,39]. The GIN and coccidia infection rates revealed in this study were relatively high.…”
Section: Plos Onesupporting
confidence: 88%
“…Both these infections display similar clinical symptoms ranging mainly from digestive tract inflammation, damage to the integrity of gastrointestinal tissues, to nutritional disorders. These result in gradual weight loss, anemia, limited growth and development, slowed weight gain, reduced efficiency of feed utilization, and exhaustion and even death in sheep in severe cases [1][2][3]. It adversely affects the quality of the skin, fur, meat, and milk production while increasing the breeding costs and decreasing the economic benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Anemia observed in this study can be attributed to the GIN, predominated by H. contortus adult worms that cause harm as they cut to the mucosal lining in the abomasum, enabling them to suck blood from the mucosa of the GIT, causing blood loss, and development of anemia in sheep [46]. These observations agree with the results of previous studies where a relationship between EPG level and FAMACHA © categories was elucidated and FAMACHA © scoring was positively correlated with FEC levels in sheep [47,48]. However, the present study was in contrast with the study conducted by Mohammed et al [49] that showed no correlation between EPG and FAMACHA © score meaning that in their study, an increase in anemia did not necessarily result in an increased EPG which could have been due to mild infection in their study animals.…”
Section: Discussionsupporting
confidence: 91%
“…The present results indicated that the BCS decreased sharply by GINs infection without garlic powder supplementation, whereas it ranged from 4.0 to 4.5 in garlic powder supplemented sheep, which reflects an improved health status of lambs supplemented with garlic powder vs. non-supplemented sheep. The improved BCS might be partly due to decreased FEC of lambs, as a negative correlation between BCS and FEC was widely found [53,54]. In addition, the increased dietary CP intake by garlic powder feeding also may have contributed to the nutritional and health enhancement of lambs, because more muscle may be deposited when the GINs burden decreased [55].…”
Section: Discussionmentioning
confidence: 99%